Rapid prototyping and engineering applications : a toolbox for prototype development - Liou, Frank W. (Taylor and Francis, CRC Press, 2019)
Since the publication of the first edition, several Additive Manufacturing technologies have been invented, and many new terminologies have been formalized. Each chapter has been brought up-to-date so that this book continues with its coverage of engineering procedures and the application of modern prototyping technologies, such as Additive Manufacturing (AM) and Virtual Prototyping (VP) that quickly develops new products with lower costs and higher quality. The examples, practice exercises, and case studies have also been updated. Features Gears toward rapid product prototyping technologies Presents a wide spectrum of prototyping tools and state-of-the-art additive manufacturing technologies Explains how to use these rapid product prototyping tools in the development of products Includes examples and case studies from the industry Provides exercises in each chapter along with solutions